Determination of lead in medicinal plants by high-resolution continuum source graphite furnace atomic absorption spectrometry using direct solid sampling - Rego, Jardes Figueredo [UNESP]; Virgilio, Alex; Nobrega, Joaquim A.; Gomes Neto, José Anchieta [UNESP] (Elsevier B.V., 2012)
A procedure is proposed for Pb determination in medicinal plants by high-resolution continuum source graphite furnace atomic absorption spectrometry (HR-CS GF AAS) using direct solid sampling. Among Pd(NO3)(2), Pd/Mg(NO3)(2). NH4H2PO4 and the W-coated platform tested as chemical modifiers, Pd(NO3)(2) presented the best performance. Calibration plots (10-1000 pg Pb) with regression coefficients better than 0.999 were typically obtained. Accuracy was checked for Pb determination in five plant certified reference materials. Results were in agreement with reference values at a 95% confidence level (paired t-test). Medicinal plant samples were analyzed by the proposed procedure and line-source GF MS using slurry sampling as a comparative technique. The RSD was 10% (n=3) for a sample containing 0.88 mu g g(-1) Pb. The limit of quantification (dry mass) was 0.024 mu g g(-1). The contents of Pb in medicinal plant samples varied in the 0.30-1.94 mu g g(-1) range. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Lead; Medicinal plant; Direct solid sampling; High-resolution continuum source graphite; furnace atomic absorption spectrometry